Study on postnatal care in a tertiary care hospital in eastern India and the reality - Das, Bharati (International Journal Of Community Medicine And Public Health, 2020)
Background: Post-natal period remains the most important time in which maximum maternal and neonatal mortality occurs. Many studies had been done on postnatal care in India also in abroad before. However, most of them were basically community-based surveys in rural areas or urban slums. The objective of the current study was to assess knowledge and practice of postnatal care services and its status in mothers in urban area. Methods: It is a prospective, hospital-based study done from February 2019 to July 2019. Data was collected by structured questionnaire method from the mothers who were coming for routine immunization for their babies at 6 weeks. Results: Total number of mothers were 214, 52.34% were delivered in medical college and DHQH and 47.66% at private sectors. Health related issues were present in 36 (16.6%) of mothers and 33 (15.4%) of babies. Only 2.8% of mothers received post-natal check-up. IFA and calcium supplementation were taken (128) 60% of mothers as opposed to advised in 151 (70.56%) of cases of varying durations. Conclusions: Post-natal care was unacceptably low despite various government programmes, well socioeconomic status, education of the mother and presence of health-related issues in the mother or the baby. Which was mainly due to lack of proper counselling for postnatal care. Strengthening the postnatal care services by sensitization of the staffs with uniform policy and mother centred counselling remains the need of the hour.